Rewilding traditional grazing areas affects scavenger assemblages and carcass consumption patterns - Arrondo, Eneko; Morales-Reyes, Zebensui; Moleón, Marcos; Cortés-Avizanda, Ainara; Donázar, José Antonio; Sánchez-Zapata, José Antonio (Basic and applied ecology, 2019)
The abandonment of traditional livestock farming systems in Mediterranean countries is triggering a large-scale habitat transformation, which, in general, consists of the replacement of open grazing areas by woodlands through non-managed regeneration. As a consequence, wild ungulates are occupying rapidly the empty niche left by domestic ungulates. Both types of ungulates represent the main trophic resource for large vertebrate scavengers. However, a comparison of how vertebrate scavengers consume ungulate carcasses in different habitats with different ungulate species composition is lacking. This knowledge is essential to forecast the possible consequences of the current farmland abandonment on scavenger species. Here, we compared the scavenging patterns of 24 wild and 24 domestic ungulate carcasses in a mountainous region of southern Spain monitored through camera trapping. Our results show that carcasses of domestic ungulates, which concentrate in large numbers in open pasturelands, were detected and consumed earlier than those of wild ungulate carcasses, which frequently occur in much lower densities at more heterogenous habitats such as shrublands and forest. Richness and abundance of scavengers were also higher at domestic ungulate carcasses in open habitats. Vultures, mainly griffons (Gyps fulvus), consumed most of the carcasses, although mammalian facultative scavengers, mainly wild boar (Sus scrofa) and red fox (Vulpes vulpes), also contributed importantly to the consumption of wild ungulate carcasses in areas with higher vegetation cover. Our findings evidence that the abandonment of traditional grazing may entail consequences for the scavenger community, which should be considered by ecologists and wildlife managers.